Efektivitas Trichoderma spp. sebagai Pengendali Hayati terhadap Tiga Patogen Tular Tanah pada Beberapa Jenis Tanaman Kehutanan - S. M. Widyastuti; Sumardi Sumardi; P. Sumantoro (Universitas Gadjah Mada, 2001)
The experiment was aimed to compare Trichoderma spp. with fungicides in the control of soil-borne pathogens and to evaluate the inhibitory effect of the fungicides on the activity of Trichoderma spp. The first objective was achieved by applying antagonistic test of three isolates of Trichoderma spp. and inhibitory growth test of fungicides both against soil-borne pathogens. The second objective was attained by growing Trichoderma spp. on growth medium containing four level of fungicides. The results showed that three isolates of Trichoderma were comparable to fungicides in their ability to inhibit root rot pathogens. T. koningii at a concentration of 103 spores/ml performed the same level of growth inhibition with that of 0.2 ppm captafol against Rigidoporus lignosus. T. reesei at a concentration of 104 spores/ml gave same inhibition effect with that of 25 ppm benomyl against Ganoderma sp., and T. harzianum at a concentration of 105 spores/ml had the same inhibition effect against Sclerotium rolfsii with captafol at a concentration of 20 ppm. The results also showed that fungicides could affect the activities of Trichoderma on the medium. Benomyl promoted the growth of T. reesei and T. harzianum at a concentration of 0.2 ppm while at a concentration of 20 ppm both of them could not grow.